(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The study examines the functions of metaphor in modern political discourse. It concentrates on the main types of Russian political metaphor and their models considering the emotivity in the political speech of two Russian presidents, which are analysed based on specific examples. In this regard, it is shown that in the Russian modern political discourse, metaphors from the conceptual spheres, such as ‘disease’, ‘culinary’, ‘human’, ‘game’ and ‘theatre’, are more often used. In order to convey a specific state, it is very convenient to refer to metaphors, which, on the one hand, can significantly soften the statement, and on the other hand, can more figuratively convey it. Metaphor is as a powerful tool for influencing the consciousness of the recipient and transforming the political worldviews. The use of metaphor, as well as various ways of highlighting it in the text, ensures its semantic and emotional integrity. Researchers point out that the influence of emotions on the formation of political preferences is not inferior to the influence of rational awareness of the problem. Moreover, most often a person primarily tends to make a decision under the influence of emotions and only afterwards tries to find a rational explanation for the decision. The features of using the main metaphorical models are shown based on public speeches, interviews, and articles by two Russian political figures: Vladimir Putin and Dmitry Medvedev. Key words: emotiology, metaphor; emotivity; emotion; surprise; political discourse; functions of metaphors.